ANALYSIS FACTORS THAT AFFECTING THE WORK COMMITMENT OF TEACHERS - M Marsofiyati; Roni Faslah (Faculty of Economics, State University of Jakarta., 2015)
The purpose of this research is to analyze the factors that affecting the work commitment of teachers.The research use descriptive quantitative method. The problem are the teachers who work without commitment, just to teach according to what was ordered by the principal. By having a high work commitment that is evident in the behavior of painstaking work, passionate, integrity of the work, responsibility, and maintain morale as educators. The results are: commitment to working both seen from the achievement an average score of 71.61, completion of the task is the highest factor in teachers' work commitment with an average score of 79.67, and development of self-efficacy is the lowest factor in teachers' work commitment with an average score of 73.00.Suggestions are: schools should give rewards to the teachers who complete the task on time and to sanction teachers who did not complete the task on time, provide education and training to the teachers continuously and sustainably as efforts to develop self-efficacy ofteachers, the teacher involvement in school activities further improved, so that the visible concern for the fate of school teachers and Teacher work program should be set up and executed in accordance with a predetermined plan.